GLYCEMIC AND LIPIDEIC STATUS IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Rao, A. Harish (Journal of Health and Allied Sciences NU, 2014)
Objective: to know the glycemic and lipidaemic status in patients with acute myocardial infarction, and with the secondary objective to know the effect of age, gender, diabetes, smoking, hypertension on fasting glucose and lipid levels.Methods and materials: The 74 patients admitted for acute myocardial infarction during the study period of one year were analysed for fasting glucose values and serum levels of total cholesterol, HDL cholesterol, LDL cholesterol and triglycerides.Results: The mean serum concentrations of total cholesterol, triglycerides, HDL cholesterol and LDL cholesterol were 233.28±45.34, 139.22±41.71, 171.43±36.53 and 27.07±36.53 respectively. Mean levels of total cholesterol, HDL cholesterol, triglycerides and fasting glucose values were not affected by age, gender, BMI, hypertension and smoking. BMI >30kg/m2 was associated with increased levels of total cholesterol(p=0.013) and LDL cholesterol(p=0.014). Also increase LDL cholesterol was seen in male gender(p=0.04). The prevalence of hypercholesterolemia, hypertriglyceridemia and low HDL cholesterol was 82.4%,77% and 78% respectively. Diabetes had no effect on lipid profile.Conclusion: our study highlighted the prevalence of dyslipidemias associated with myocardial infarction but not significant impact of fasting glucose levels.
Keywords: fasting glucose; lipidemic status; myocardial infarction; coronary heart disease